2015
DOI: 10.1111/clr.12604
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic hygiene and functional efficacy in completely edentulous patients: satisfaction and quality of life during a 5‐year follow‐up

Abstract: Satisfaction among these completely edentulous patients varied in relation to prosthetic type. The level of general satisfaction among patients with implant-supported prostheses was greater than the group using conventional dentures. Patients rehabilitated with fixed prostheses enjoyed a higher level of satisfaction than patients with overdentures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…In contrast, compression of denture bearing mucosa of conventional dentures during chewing and biting limits muscle action and decreases masticatory function (Elsyad & Khairallah, ). The increased chewing ability with FP compared to MB was in line with Brennan et al () and Martin‐Ares et al () who found that satisfaction with chewing capacity, mastication, and comfort with eating were significantly higher with implant fixed prostheses than implant overdentures. Similarly, Feine et al () found that patients who gave priority to stability and chewing ability preferred the fixed prostheses over removable prosthesis.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, compression of denture bearing mucosa of conventional dentures during chewing and biting limits muscle action and decreases masticatory function (Elsyad & Khairallah, ). The increased chewing ability with FP compared to MB was in line with Brennan et al () and Martin‐Ares et al () who found that satisfaction with chewing capacity, mastication, and comfort with eating were significantly higher with implant fixed prostheses than implant overdentures. Similarly, Feine et al () found that patients who gave priority to stability and chewing ability preferred the fixed prostheses over removable prosthesis.…”
Section: Discussionsupporting
confidence: 85%
“…(); Martínez‐González et al. (); Martín‐Ares, Barona‐dorado, Guisado‐moya, Martínez‐rodríguez, & Martínez‐gonzález, ; Oh et al., ). However, two of them took items from OHIP‐14 in order to create a modified questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…However, two of them took items from OHIP‐14 in order to create a modified questionnaire. Therefore, wording of the items was inconsistent (Martín‐Ares et al., ; Martínez‐González et al., ). Regarding evaluation of patient satisfaction, no standard questionnaire was found in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…54 The patients' age could be considered an influencing factor for selection of the type of rehabilitation. 55,56 Two studies were dealing with patients of average age 64 and 67.8 years. 50.52 While in the remaining three studies younger age were included as the age ranged from second to seventh decades, 32,49-52 so all studies included all variation of age.…”
Section: Discussion:-mentioning
confidence: 99%
“…49,52,[55][56][57][58][59][60][61] Regarding the tumor stage, several studies reported that QoL is lower in patients who have large tumors and late stage. [58][59][60][61] In our search, only one study reported tumor stage, However, the data in the this study suggested that all approaches should be discussed with the patients without concern about the stage of tumors.…”
Section: Discussion:-mentioning
confidence: 99%